Der Müller Peter and (s) Fischers Emma - Theresa Schweden (Nordisk Tidskrift för Socioonomastik, 2025)
In German dialects and in rural communities, special personal names are used, in which the surname precedes the given name: der Müller Peter, Fischers Emma. This article presents the results of a research project addressing the grammatical and pragmatic variation of these unofficial names. A mixed methods approach shows that the order of “surname + given name” is triggered by dialect area, the size of a village or town, the age of the speakers, as well as the integration of a referent into the local community. Some unofficial names show remnants of genitive inflection, which has otherwise disappeared in German dialects: Fischer-s Emma. In some cases, we also find cliticized genitive articles: des > s Fischer-s Emma. A diachronic analysis shows that these structures can be traced back to possessive constructions, in which children or wives were assigned to a head of household. Even today, it is still highly relevant in rural communities to identify a person as a member of a local family.